The Imaginary and its Intellectual and Political References - Hameed, Asmaa; AlMohammadawi, Ali (Al-Adab Journal, 2024)
The issue of intellectual references and how to safeguard society from their political implications in the face of potential divisions deserves intense scrutiny for several reasons. This matter has captured the attention of many philosophers, including Charles Taylor, who has been politically and theoretically engaged for a considerable period. This research embarks on an exploratory journey, analytically examining the concept of the "imaginary" and investigating its intellectual and political references. It particularly focuses on the historical and philosophical context related to the philosopher Taylor. The aim of the study is to comprehend the vital role played by the imaginary in Taylor's worldview and its alignment with his philosophical reasoning and political beliefs.